Fabrication of a nanocomposite film decorated with highly dispersive nanoparticles by following an interface-induced strategy. Issue 47 (24th May 2022) - Ma, Rui; Huang, Yue; Huang, Jiaqi; Zheng, Kaixuan; Jiang, Shujuan; Jin, Qiao; Sun, Wei
Abstract : A polymer nanocomposite film decorated with highly dispersive nanoparticles was prepared by a liquid–liquid interface induced self-assembly method. Abstract : A polymer nanocomposite film decorated with highly dispersive nanoparticles was prepared by a liquid–liquid interface induced self-assembly method based on a breath figure process. The distribution as well as the orientation preference of the Janus particles within the polymer matrix could be dynamically controlled by adjusting the environmental conditions. Antibacterial and photocatalytic functionality was obtained for the nanocomposite films decorated with silver and titanium dioxide nanoparticles, respectively.